2002
DOI: 10.1086/341234
|View full text |Cite
|
Sign up to set email alerts
|

Intron-Size Constraint as a Mutational Mechanism in Rothmund-Thomson Syndrome

Abstract: Rothmund-Thomson syndrome (RTS) is an autosomal recessive disorder caused by deleterious mutations in the RECQL4 gene on chromosome 8. The RECQL4 gene structure is unusual because it contains many small introns <100 bp. We describe a proband with RTS who has a novel 11-bp intronic deletion, and we show that this mutation results in a 66-bp intron too small for proper splicing. Constraint on intron size may represent a general mutational mechanism, since human-genome analysis reveals that approximately 15% of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 12 publications
1
56
0
1
Order By: Relevance
“…12 Consequently, intronic size constraint and point mutations in the introns of the RECQL4 gene have been shown to play a role in the development of RTS in addition to exonic defects. [12][13][14] A cohort study of 33 patients showed that in about 57% of RTS cases, mutations of both RECQL4 alleles can be detected. Only 1 allele was found to carry a missense or a deleterious mutation in another 27% of the individuals with this disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Consequently, intronic size constraint and point mutations in the introns of the RECQL4 gene have been shown to play a role in the development of RTS in addition to exonic defects. [12][13][14] A cohort study of 33 patients showed that in about 57% of RTS cases, mutations of both RECQL4 alleles can be detected. Only 1 allele was found to carry a missense or a deleterious mutation in another 27% of the individuals with this disorder.…”
mentioning
confidence: 99%
“…16 The prevalence of osteosarcoma for patients with RAPADILINO (7%) is apparently lower than for a cohort of patients with RTS and RECQL4 mutations. 6,[13][14][15][16][18][19][20] However, no study has clearly documented the risk of osteosarcoma over time in patients with RAPADILINO.…”
mentioning
confidence: 99%
“…Both the minisatellite and the SNPs belonging to high-score motifs for SR proteins may play a role in RECQL4 mRNA missplicing, which also seems to be common in wild-type subjects (Wang et al 2002;Beghini et al 2003).…”
Section: Putative Role Of Recql4 Polymorphisms In Missplicingmentioning
confidence: 99%
“…Identification of two novel RECQL4 exonic SNPs and genomic characterization of the IVS12 minisatellite Received: October 24, 2002/ Accepted: November 21, 2002 MIM#268400; Kitao et al 1999b;Lindor et al 2000;Wang et al 2002;Balraj et al 2002), a rare autosomal recessive genodermatosis, which, in addition to the poikilodermatous rash, has a variable clinical presentation and is associated with genomic instability and predisposition to malignancy (Wang et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation